(untitled) (Bangladesh Journal of Animal Science, 2017)
This study was undertaken to compare the growth performance and nutrient digestibility (energy, protein and amino acid) of broilers fed diets containing only vegetable protein (soybean) with birds that received Pro-EL as protein supplement in their diets. Day-old male broiler chicks (n=60; Cobb 500) were randomly distributed into 2 dietary treatment groups, namely control (T1) and supplemented (T2) diets, with 5 birds per replication in a CRD. Birds had a free access to iso-caloric and iso-nitrogenous starter diets in cages up to 21d. The results of FI, LW, LWG and FCR of broilers up to 21 days were poorer (P<0.01) on T2 diet than the broilers fed on T1 diet. The ileal nutrient digestibility of GE and CP was identical (P>0.05), but the majority of the AAs digestibility values were influenced (P<0.05; P<0.01) by treatments except for Gly, Thr, Cys, Val, Ile, Leu, and Phe. The digestibility of Asp, His, Arg, Ala, Pro, Ser, Glu, Tyr and Lys was impaired (P<0.05; P<0.01) in the T2 diet compared to T1 diet except for Met, which was improved (P<01) in T2 diet. It can be concluded that the negative response of broilers fed on protein supplemented diet might arise from the reduced nutrient digestibility of the diet. Bang. J. Anim. Sci. 2017. 46 (1): 44-50